Parenting Islam dalam Menekan Kecanduan Game Online pada Remaja - Iqbal Bafadal (Universitas Islam Negeri (UIN) Mataram, 2021)
This research is motivated by the author's attention to online game addiction in adolescents. The focus studied in this study is how the Islamic parenting method in tackling teenagers who are addicted to online games. This study uses a qualitative approach through data collection with an interview, observation, and documentation techniques. The results of this study show that teenagers need a long time to play online games starting from 3 hours to 18 hours every day so that it can interfere with other activities, weak parenting from parents provides opportunities for children to play online games as widely as possible. The breadth, as well as the Islamic parenting method that is carried out and given maximally by parents, can suppress addiction and dependence on online games through exemplary methods, habituation, advice, attention, and punishment.